2016
DOI: 10.1038/srep19969
|View full text |Cite
|
Sign up to set email alerts
|

Precision Medicine: Genetic Repair of Retinitis Pigmentosa in Patient-Derived Stem Cells

Abstract: Induced pluripotent stem cells (iPSCs) generated from patient fibroblasts could potentially be used as a source of autologous cells for transplantation in retinal disease. Patient-derived iPSCs, however, would still harbor disease-causing mutations. To generate healthy patient-derived cells, mutations might be repaired with new gene-editing technology based on the bacterial system of clustered regularly interspersed short palindromic repeats (CRISPR)/Cas9, thereby yielding grafts that require no patient immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(78 citation statements)
references
References 15 publications
1
71
0
6
Order By: Relevance
“…Thus, the future management of IBD should also consider the paradigm changing opportunities (and challenges) in precision medicine. Looking to the field of oncology, promising advancements are being described whereby individual therapies are constructed and/or screened based specifically on the molecular features of an individual's tumour profile 125 126. The application of such precision medicine methods for IMIDs should also be considered, and in fact, the future of clinical testing of individuals for unique biomarker profiles that direct specific therapies in such conditions is here 127…”
Section: Future Directionsmentioning
confidence: 99%
“…Thus, the future management of IBD should also consider the paradigm changing opportunities (and challenges) in precision medicine. Looking to the field of oncology, promising advancements are being described whereby individual therapies are constructed and/or screened based specifically on the molecular features of an individual's tumour profile 125 126. The application of such precision medicine methods for IMIDs should also be considered, and in fact, the future of clinical testing of individuals for unique biomarker profiles that direct specific therapies in such conditions is here 127…”
Section: Future Directionsmentioning
confidence: 99%
“…Bassuk et al 8 reported that this system can be used to repair genetic defects in stem cells of patients suffering from retinitis pigmentosa. They showed that 13% of the defective gene copies could be completely replaced by the corrected copy.…”
Section: Redesigning Nature: Use Of Cas/crispr In Genome Editingmentioning
confidence: 99%
“…crRNAs can recognize the exogenous genome if a viral reinfection occurs. through CRISPR/Cas9 approach (19), which opens a promising era in regenerative medicine and genome engineering.…”
Section: Precision Medicine: Crispr/cas9 Genome Editingmentioning
confidence: 99%
“…Utilization of patient's cells in order to avoid ethical concerns and rejection complications is possible by cellular reprogramming, particularly iPSCs technology (19).…”
Section: Precision Medicine: Crispr/cas9 Genome Editingmentioning
confidence: 99%